Natural history of progressive supranuclear palsy (Steele-Richardson-Olszewski syndrome) and clinical predictors of survival: a clinicopathological study. Issue 6 (June 1996) - Litvan, I; Mangone, C A; McKee, A; Verny, M; Parsa, A; Jellinger, K; D'Olhaberriague, L; Chaudhuri, K R; Pearce, R K
Abstract : OBJECTIVE--To analyse the natural history of progressive supranuclear palsy (PSP or Steele-Richardson-Olszewski syndrome) and clinical predictors of survival in 24 patients with PSP confirmed by necropsy, who fulfilled the NINDS criteria for a neuropathological diagnosis of typical PSP. METHODS--Patients were selected from the research and clinical files of seven medical centres involving tertiary centres of Austria, England, France, and the United States. Clinical features were analysed in detail. The patients' mean age at onset of PSP was 63 (range 45-73) years. RESULTS--The most frequent clinical features (occurring in at least 75% of the patients) were early postural instability and falls, vertical supranuclear palsy, akinetic-rigid predominant parkinsonian disorder characterised by symmetric bradykinesia and axial rigidity unrelieved by levodopa, pseudobulbar palsy, and frontal release signs. Occasionally, segmental dystonia or myoclonus were described, but neither aphasia nor alien limb syndrome was reported. Fractures occurred in 25% of the patients but were unrelated to the severity of the gait or to the presence of falls. Median survival time was 5.6 (range 2-16.6) years. Onset of falls during the first year, early dysphagia, and incontinence predicted a shorter survival time. Age at onset, sex, early onset of dementia, vertical supranuclear palsy, or axial rigidity had no effect on prognosis of survival. Pneumonia was the most common immediate cause of death. PSP was most often clinically misdiagnosed as Parkinson's disease. Errors in diagnosis suggest that PSP is underdiagnosed. CONCLUSION--Progressive onset of early postural instability with falls or supranuclear vertical palsy in the fifth decade, should suggest the diagnosis of PSP. Onset of falls during the first year are emphasised, as they could lead to an early diagnosis and influence the prognosis of patients with PSP. Whether appropriate treatment of the dysphagia could prolong the survival of PSP patients needs to be explored.